PENGARUH PERSONAL COST OF REPORTING, KOMITMEN ORGANISASI, DAN SIKAP PADA FISKUS TERHADAP INTENSI MELAKUKAN TINDAKAN PELAPORAN KECURANGAN (WHISTLEBLOWING) - Alfallah, Miftha Pasha; Damayanti, Damayanti; Puspitasari, Endah Yuni (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to see how personal cost of reporting, organizational commitment, and attitudes influence the intention of employees tax on reporting violations (whistleblowing). Data collection techniques in this study used primary data, namely questionnaires distributed to respondents at the research object, namely the Pratama Natar Tax Service Office. The selection of the sample in this study used non-probability sampling, namely the type of saturated or census sampling, where each member of the population was taken as a sample of 102 respondents with a return rate of 98%, so that a total of 100 questionnaires. Completed questionnaires will be processed using SPSS software version 26, using multiple regression analysis techniques. The results of data processing can be concluded that personal cost of reporting has a positive effect on whistleblowing intentions with a significance value of 0,026 < 0,05 so that the first hypothesis is accepted. For the Organizational Commitment variable there is a positive influence on whistleblowing intentions with a significance value of 0,001 < 0,05 so the second hypothesis is accepted. And for the attitude variable it is concluded that there is a positive influence on whistleblowing intentions with a significance value of 0,010 < 0,05 so that the third hypothesis can be said to be accepted.